T6 Randomised sham-controlled trial of transcutaneous electrical stimulation in obstructive sleep apnoea. (15th November 2016) - Pengo, M; Sichang, X; Ratneswaran, C; Shah, N; Reed, K; Chen, T; Douiri, A; Hart, N; Luo, Y; Rafferty, G; Rossi, GP; Williams, A; et al.
Abstract : Obstructive sleep apnoea is characterised by a loss of neuromuscular tone of the upper airway dilator muscles while asleep. Continuous positive airway pressure is a well-established long-term treatment, but patient compliance is limited. This study investigated the effectiveness of transcutaneous electrical stimulation in patients with obstructive sleep apnoea. This was a randomised, sham-controlled cross-over trial using transcutaneous electrical stimulation of the upper airway dilator muscles in patients with confirmed obstructive sleep apnoea. Patients were randomly assigned to two nights, sham stimulation and active treatment. The primary outcome was the 4% oxygen desaturation index, responders were defined as patients with a reduction >25% in the oxygen desaturation index when compared to sham stimulation and/or with an index <5/hour in the active treatment night. In 36 patients (age mean 50.8 (standard deviation 11.2) years, male/female 30/6, body-mass-index median 29.6 (interquartile range 26.9–34.9) kg/m 2, Epworth Sleepiness Scale 10.5 (4.6) points, oxygen desaturation index median 25.7 (16.0–49.1)/hour, apnoea hypopnoea index median 28.1 (19.0–57.0)/hour) the primary outcome measure improved when comparing sham stimulation (median 26.9 (17.5–39.5)/hour) to active treatment (median 19.5 (11.6–40.0)/hour; p = 0.026), a modest reduction of the mean by 4.1 (95% CI: −0.6–8.9)/hour. Secondary outcome parameters of patients' perception indicated that stimulation was well tolerated. Responders (47.2%) were predominantly from the mild-moderate obstructive sleep apnoea category. In this subgroup, the oxygen desaturation index was reduced by 10.0 (95% CI: 3.9–16.0)/hour (p < 0.001) and the apnoea hypopnoea index was reduced by 9.1 (95% CI: 2.0–16.2)/hour (p = 0.004). Transcutaneous electrical stimulation of the pharyngeal dilators during a single night in patients with obstructive sleep apnoea improves upper airway obstruction and is well tolerated. (TESLA trial registration at NCT01661712 )